Could use of informal healthcare providers increase uptake of HIV testing? Qualitative results from southwestern Uganda - Matthew Ponticiello, BS; Juliet Mwanga-Amumpaire, MD; Denis Nansera, MD; Rachel King, PhD; Radhika Sundararajan, MD (Elsevier, 2021)
Background: Uganda is an HIV-endemic country with prevalence of around 6%, and has yet to reach the 95-95-95 UNAIDS benchmarks for HIV epidemic control. It has previously been reported that approximately 80% of people in sub-Saharan Africa use informal health-care providers such as traditional healers. Collaboration with informal healthcare providers has been proposed as a strategy to increase testing uptake. In this study, we use data from a parent cluster-randomised trial and aim to assess acceptability and implementation of a programme that uses informal health-care providers to deliver point-of-care HIV testing. Methods: We analysed qualitative data from a parent cluster-randomised trial in which traditional healers delivered oral swab point-of care HIV tests to adults of unknown HIV serostatus (clinicaltrials.gov NCT#03718871). We invited traditional healers aged 18 years or older who were practising within 10 km of Mbarara township, southwestern Uganda, to participate in the trial. We recruited a purposive sample of trial participants to complete a qualitative interview. We included patients who had received care from participating healers, were aged 18 years or older, were sexually active, self-reported not receiving an HIV test in the previous 12 months, and had not previously been diagnosed with HIV infection. Interviews explored experiences of participating in the trial and perceptions of healers delivering HIV testing. Interviews were audio-recorded, conducted in the local language, then translated and transcribed into English. Following a content-analysis approach, transcripts were independently reviewed by two authors to develop a coding scheme and framework that explains outcomes of the parent trial. Findings: Between Nov 26, 2019, and May 14, 2020, we conducted 124 interviews with 17 traditional healers and 107 trial participants. Half the participant group were women (n=62, 50%) and approximately one-third of healers were women (n=6, 35%). Responses from patients and providers showed that the intervention programme mitigated existing barriers to HIV testing. First, healer-delivered HIV testing overcame structural barriers that impeded receiving tests at clinical facilities. Underlying impoverishment and rural locations limited use of clinical testing, as transportation costs to facilities were frequently prohibitive. Healers were located in villages, where their services were easier to access. Second, patients perceived traditional healers as trustworthy and confidential. Participant responses underscored a preference for receiving an HIV test from a healer, rather than from biomedical settings, where HIV testing was described as stigmatising. Additionally, traditional healers reported increased respect from community members for offering HIV testing and expressed a desire to continue to offer HIV testing and counselling. Interpretation: Use of informal health-care providers to administer HIV testing is not only feasible but also well accepted in an area where traditional healers are frequently used for health care. Healers should be considered key stakeholders in the effort to increase uptake of HIV testing and achieving HIV epidemic control. Further research should consider whether results are generalisable beyond rural Uganda. Funding: National Institutes of Mental Health (K23MH111409 PI: [RS]).